Virtual Distributed Supervision and Control for an Automated Greenhouse. - Hernández Camacho, Jorge; Muñoz Hernández, Laura E.; Acosta Guadarrama, Juan Carlos; López Morales, Virgilio (Ciencia Huasteca Boletín Científico de la Escuela Superior de Huejutla, 2014)
In order to have an optimal production in a Green-house, it is necessary to regulate the artificial micro-environment. By controlling the main physical variables (temperature, humidity, irrigation cycles, etc.) as well as the variables involved in the rates of plants growing (nutrients, sun radiation, water, etc.), the plant’s production quality, the energy and water consumption can be optimized. For instance, temperature and humidity can be regulated by opening or drawing the ventilation system or domes or by heating or circulating the air inside the greenhouse. These tasks should be constantly supervised by a supervised distributed communication system. In this paper, we propose a distributed serial communication system based on microcontrollers to monitoring and supervising the process via Internet, in order to achieve the on-line supervision and control of the greenhouse operation and environmental conditions as well as the main variables (temperature, humidity, irrigation cycles, etc.).